Determinants of Livestock Insurance Adoption by Dairy Cattle Farmers of Nawalpur District, Nepal - Mishra, B.P.; Singh, O.P. (NPI Journal of Science and Technology, 2024)
Livestock farming faces inherent vulnerabilities, such as disease outbreaks and natural disasters. The utilization of livestock insurance can play a crucial role in alleviating risks and uncertainties associated with farming practices, ultimately fostering security for farmers. The research was carried out purposively in Nawalpur district during 2022 to identify the factors affecting adoption of livestock insurance among dairy cattle farmers. One hundred and twenty dairy cattle farmers were selected randomly from the study area. Primary data were collected using pretested semi-structured interview schedule, Focus Group Discussion and Key Informant Interview. Descriptive statistics and probit model were used to interpret the findings. Findings from the research revealed that age, membership in farmer’s organization, contact with extension worker and rearing of improved breed were statistically significant in the adoption of livestock insurance. Extension agencies of government, non-governmental institution and insurance companies should primarily focus on farmers who are old aged, rear improved breed, participate in farmer’s organization and have regular contact with extension worker for better adoption.